Synthesis and Evaluation of Novel [1, 2, 4]Triazolo[5, 1‐c][1, 2, 4]‐triazines and Pyrazolo[5, 1‐c][1, 2, 4]triazines as Potential Antidiabetic Agents. Issue 5 (10th April 2017) - Rusinov, Vladimir L.; Sapozhnikova, Irina M.; Bliznik, Anastasiya M.; Chupakhin, Oleg N.; Charushin, Valery N.; Spasov, Alexander A.; Vassiliev, Pavel M.; Kuznetsova, Valentina A.; Rashchenko, Andrey I.; Babkov, Denis A.
Abstract : Inhibition of the dipeptidyl peptidase‐4 (DPP4) enzyme activity and prevention of advanced glycation end (AGE) products formation represents a reliable approach to achieve control over hyperglycemia and the associated pathogenesis of diabetic vascular complications. In the frames of this research study, several triazolo‐ and pyrazolotriazines were synthesized and evaluated as inhibitors of AGE products formation, DPP4, glycogen phosphorylase and α‐glucosidase activities, as well as AGE cross‐link breakers. From the two considered classes of heterocyclic compounds, the pyrazolotriazines showed the highest potency as antiglycating agents and DPP4 inhibitors. Structure–activity relationships (SAR) for these compounds, which can be considered as potential drugs for the treatment of type 2 diabetes, were evaluated. Abstract : A series of novel azolo[5, 1‐ c ][1, 2, 4]triazines were synthesized and evaluated as inhibitors of advanced glycation end (AGE) products formation, dipeptidyl peptidase 4, glycogen phosphorylase and α‐glucosidase activities, and as AGE cross‐link breakers. One of the most active compounds (16a ) inhibits methylglyoxal‐mediated AGE products formation with an IC50 value of 186.8 μM.